ANALISIS FAKTOR –FAKTOR YANG MEMPENGARUHI MINAT SISWA KELAS XII JURUSAN AKUNTANSI DAN KEUANGAN LEMBAGA SMKS PELITA GAMA PENAJAM DALAM MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI PROGRAM STUDI AKUNTANSI - Endi Gunawan (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The purpose of this study is to identify the determining factors of academic interest among twelfth – grade students in the Accounting and Financial Institution program at SMKS Pelita Gama Penajam in continuing their education to an accounting study program at a university. This study employs a quantitative descriptive methodology, focusing on factor analysis as its primary tool. The participants consist of 20 twelgth-grade students from Accounting and Financial Institution Program at SMKS Pelita Gama Penajam. Data were collected using a closed questionnaire with a Likert scale. The results showed that most students (18 students) were not interested in continuing their studies in the accounting study program because they chose to work after graduation. The most influential internal factor was